Discretionary power of the judge in making the conciliation interpretation of the contract - Huasain, Esmail Namiq; Brakhas, Asos Namiq (Journal of Legal and Political Studies, 2021)
The conciliatory interpretation depends on the authority that the judge wields during the interpretation, so the extent of this authority affects the interpretation process and the legal outcome that emerges from reality. This authority is based on many objective controls that restrict dealing with the law on the one hand and with the terms of the contract on the other hand, as well as being influenced by factors that affect the contract itself, except for internal factors derived from the contract itself or external factors outside the contract but affected by the contract. and influence its interpretation, and the interpretation process is subject to discriminatory control. However, this oversight is tightened in matters of law, and is reduced or disappeared whenever the issue is a matter of reality.
Keywords: conciliatory interpretation; legal outcome; external factors; objective controls; wields